Objective evaluation of out-of-competition volume of action in wheelchair basketball classification - Shimoyama, Y.; Kasai, S.; Wagatsuma, H.; Ibusuki, T.; Tsukada, T.; Tachibana, K. (Sports, 2025)
In wheelchair basketball, classes are based on competition observations. Since 2021, out-of-competition testing has been implemented; however, research remains limited. This study aimed to determine whether the quantified volume of action (VOA) can be an indicator for classification and examined the influence of a competitive wheelchair on VOA evaluation. This cross-sectional study included 47 wheelchair basketball players (21 able-bodied, 26 with physical impairments: class 1, n = 8; class 2, n = 5; class 3, n = 4; class 4, n = 9). Tests were performed in a wheelchair (wheelchair condition) and on a trainer bed (bed condition). Participants held a ball and rotated their trunks in various planes. Movements were recorded using four cameras, and position coordinates were extracted using the three-dimensional DLT method. Classes and sitting conditions were compared across five groups: classes 1, 2, 3, 4, and able-bodied. Comparisons between classes revealed significant differences in all planes, including wheelchair and bed conditions (p < 0.05). The VOA expanded in the wheelchair condition compared to the bed condition across multiple classes and planes (p < 0.05). Measuring the VOA outside the competition while sitting on a bed may effectively classify players by eliminating equipment influence.